The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1126/science.1113109
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence and Lytic Phase Transcription Profile of a Coccolithovirus

Abstract: The genus Coccolithovirus is a recently discovered group of viruses that infect the globally important marine calcifying microalga Emiliania huxleyi. Among the 472 predicted genes of the 407,339-base pair genome are a variety of unexpected genes, most notably those involved in biosynthesis of ceramide, a sphingolipid known to induce apoptosis. Uniquely for algal viruses, it also contains six RNA polymerase subunits and a novel promoter, suggesting this virus encodes its own transcription machinery. Microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
337
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(343 citation statements)
references
References 24 publications
5
337
1
Order By: Relevance
“…It is intriguing that, so far, not much interest has been devoted to the lipid inventory of viruses, much in contrast to viral genomes and proteins. This is largely due to the fact that only very few virus encoded lipid enzymes are known [6]. Instead, viruses derive their lipids from the host.…”
Section: Enveloped Viruses (Human Immunodeficiency Virus)mentioning
confidence: 99%
“…It is intriguing that, so far, not much interest has been devoted to the lipid inventory of viruses, much in contrast to viral genomes and proteins. This is largely due to the fact that only very few virus encoded lipid enzymes are known [6]. Instead, viruses derive their lipids from the host.…”
Section: Enveloped Viruses (Human Immunodeficiency Virus)mentioning
confidence: 99%
“…A range of different viruses that infect E. huxleyi (EhV) were isolated from the English Channel and off the coast of Bergen, Norway (Castberg et al, 2002, Wilson et al, 2002b and were analysed for their phylogeny (Schroeder et al, 2002), ecological successions in mesocosm experiment (Schroeder et al, 2003) and genome structure (EhV-86) (Allen et al, 2006, Wilson et al, 2005. Characterization of their sequences revealed that the E. huxleyi viruses are large double-stranded DNA viruses with genomes approximately 410 kbp in size and that they belong to a new virus genus termed Coccolithovirus based on the phylogeny of their DNA-polymerase gene (Schroeder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of their sequences revealed that the E. huxleyi viruses are large double-stranded DNA viruses with genomes approximately 410 kbp in size and that they belong to a new virus genus termed Coccolithovirus based on the phylogeny of their DNA-polymerase gene (Schroeder et al, 2002). Coccolithoviruses belong to the Phycodnaviridae (Wilson et al, 2005), a diverse family of large icosahedral viruses that infect marine or freshwater eukaryotic algae. They all contain dsDNA genomes ranging from 180-560 kb (Van Etten et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…E. huxleyi blooms are routinely infected and terminated by specific giant double-stranded DNA coccolithoviruses (Phycodnaviridae) (Bratbak et al, 1993;Brussaard et al, 1996;Schroeder et al, 2002;Wilson et al, 2002;Lehahn et al, 2014), the E. huxleyi virus (EhV), which is part of the nucleocytoplasmic large DNA virus (Asfarviridae, Ascoviridae, Iridoviridae, Marseilleviridae, Megaviridae, Mimiviridae, Pandoraviridae, Phycodnaviridae, Pithoviridae and Poxviridae) clade. EhV encodes for an almost complete de-novo biosynthetic pathway for ceramide (Wilson et al, 2005), a sphingolipid known to induce apoptosis in animals and plants (Pettus et al, 2002;Liang et al, 2003). This pathway was recently shown to have a critical role in EhV replication and in induction of E. huxleyi programmed cell death in cultures and during natural bloom demise (Pagarete et al, 2009;Vardi et al, 2009Vardi et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%